A structural investigation of the sulphated polysaccharide of Anathaca dentata (suhr) papenf. and the xylan of Chaetangium erinaceum (turn.) papenf. - Russell, Irina (Rhodes University, Faculty of Science, Department of Chemistry, 1972)
Hot-water extraction of Anatheca dentata, a red seaweed belonging to the family Solieriaceae, yielded a mixture of polysaccharides. Fractionation of this mixture with Cetavlon gave a glucomannan as minor component and a highly sulphated major component, which gave D- and L-galactose, D-xylose and small amounts of 3-0 (underscore)-methylgalactose, pyruvic acid and uronic acid on hydrolysis. All subsequent investigations were carried out on the sulphated major component. The sulphate was not labile to alkali, but was removed with methanolic hydrogen chloride. Periodate oxidation of the polysaccharide before and after desulphation indicated that new a-glycol groups were formed during desulphation. All the xylose units in the polymer were cleaved by periodate and this, together with the fact that the major xylose product from methylation analysis of the desulphated polymer was the 2,3, 4-tri-0 (underscore)-methyl derivative, indicated that the xylose occurs as a non-reducing end-group. Methylation of the desulphated polysaccharide revealed the presence of 1,4- and 1,3- linked D- galactose and 1,4- linked L-galactose units in the polymer. D-Glucuronic acid occurred as non-reducing end-groups. Summary, p. 1.
Keywords: Polysaccharides; Marine algae -- Composition